A dinâmica de conhecimento e inovação no setor elétrico brasileiro: proposta de um conjunto de indicadores gerenciais - Fabricio Ziviani (2012)
The process of measuring innovation performance is critical to evaluate factors such as impacts, investments and achieve the expected result. Indicators are an excellent tool for measuring the performance of the innovation effort of an organization and support managers with information to support decision making. In the late 90s, the Brazilian government has determined that the electric companies for generation,transmission and distribution to apply 1% of their net operating revenues in R&D and energy efficiency.In this new business landscape, provide energy services with quality, safety, environmental sustainability and low tariffs requires more than leadership in specific segments, we need broad field of technology-based supply chain and nanostructured materials, among other items whose field of technology has been the privilege of a few countries. Over the first ten years of the new model ofR&D in the energy sector, about one and a half billion reais invested thousands of projects were developed and hundreds of research institutions and highly skilled professionals were involved in the process. In this context, this study aims to examine organizational practices related to innovation activity present in the Brazilian electric sector companies and propose indicators to monitor its evolution in the management of information, knowledge and innovation. This is a research approachwith quantitative descriptive in nature. We chose to use the survey as a research strategy. The questionnaire prepared for this survey was structured into five distinct parts, having used sets of items (questions) to measure: the characteristics of the group; practices related to innovation management; indicators for assessing the impacts of innovation; sources innovation and the factors that affect innovation activities. The questionnaire followed a matrix structure of responses using Likertscales five points. We applied 120 questionnaires to managers and / or responsible for R&D activity in the organizations under study. To represent each point of analysis, an index was created by averaging the questions on standardized scale, through which it is possible: to reduce the measurement error of a single question; represent the many facets of the concept relative to the index. Furthermore the scale is easily to apply in other studies. Seven indices were constructed for practices related toinnovation management, five indices for the indicators in assessing the impacts of innovation, an index that represents all sources of innovation and an index that represents all factors that hamper innovation activities. The indices vary in a range from -1 to 1. All are conceptually well defined and have been validated by criteria. It is noteworthy that the proposition of the indicator set is a starting point for discussion of how to measure aspects of practices and indicators related to innovation in the electricity sector.